In silico identification of PPARγ agonists from diffractaic acid analogs in prostate cancer: a comprehensive computational approach - Roney, Miah; Uddin, Md. Nazim; Ali Khan, Azmat; Mohd Fadhlizil Fasihi, Mohd Aluwi; Fatima, Sabiha; Ahmad, Asrar (Springer Science and Business Media Deutschland GmbH, 2025)
Prostate cancer (PCa) is the second most frequent and the fifth greatest cause of death in men. Although there are already therapies for early-stage PCa, their effectiveness in advanced PCa is limited, primarily because of medication resistance or poor efficacy. To find new therapeutic indications or repurpose current medications, this project intends to use computational approaches to investigate possible anti-PCa compounds based on simulated screening of FDA-approved drug bank databases. The techniques used in this study include virtual screening of the drug bank database utilising a matrix or user molecule (Diffractaic acid; DA), integrated network pharmacology, molecular docking, detailed molecular dynamic simulation. The results showed that 18 DA analogues in total were chosen from the drug bank database and put through integrated network pharmacology. The KEGG enrichment analysis indicated that hsa05215: Prostate cancer is one of the most significant PCa enrichment signalling pathways which exhibited 18 protein–protein interactions including PDGFRB, PDGFRA, PPARG, GSK3B, MAP2K1, CREBBP, HSP90AA1, HSP90AB1, CHUK, PIK3CD, BRAF, PIK3CB, MTOR, AR, PIK3CA, PLAU, CDK2, and MAPK1. Subsequent molecular docking study with the best target protein (PPARγ) showed that the DB14929 molecule formed hydrogen bonds with the Gln273, Arg280, Arg288, and Ser342 residues and exhibited a high binding affinity ( − 10.5 kcal/mol) for the PPARγ agonist against PCa. Furthermore, molecular dynamic simulation showed that DB14929 formed a stable protein–ligand complex with RMSD, RMSF, Rg, and SASA values. Furthermore, the dynamic behaviour of the PPARγ protein linked to DB14929 in its conformational space was analysed using the PCA technique, demonstrating the excellent conformational space behaviour. Additionally, the free binding energy value of − 57.15 kcal/mol of DB14929 indicated that it could be an agonist of PPARγ of PCa.